An international research on the influence of accreditation on academic quality - BAKİOĞLU, AYŞEN (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2019)
Due to increasing demand for higher education around the world, concerns regarding the quality of education in higher education institutions have increased. The aim of this study was to determine perceptions of accreditation self-study coordinators and programme administrators on the influence of accreditation on academic quality. Data was collected by means of a scale devised by researchers. To achieve this, a comprehensive literature review was conducted, a pilot scheme was administered, expert opinion and advice were obtained and validity and reliability studies were conducted. The findings revealed that accreditation contributes more to the improvement of processes and practices in institutions in operation for 1-20 years compared to those functioning for more than 41 years. Similarly, accreditation makes a greater contribution during the initial accreditation process compared to re-accreditation. Additionally, accreditation contributes most to importance attached to learning outcomes and least to the number of students who graduate from a programme.
Keywords: Accreditation; academic quality; higher education; international education; quality; HIGHER-EDUCATION; STANDARDS; PERFORMANCE; ASSURANCE